2017
DOI: 10.3389/fnmol.2017.00325
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Hippocampal 5-HT Release by P2X7 Receptors in Response to Optogenetic Stimulation of Median Raphe Terminals of Mice

Abstract: Serotonergic and glutamatergic neurons of median raphe region (MRR) play a pivotal role in the modulation of affective and cognitive functions. These neurons synapse both onto themselves and remote cortical areas. P2X7 receptors (P2rx7) are ligand gated ion channels expressed by central presynaptic excitatory nerve terminals and involved in the regulation of neurotransmitter release. P2rx7s are implicated in various neuropsychiatric conditions such as schizophrenia and depression. Here we investigated whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…However, the specific purinergic receptor subtype involved in this effect was not characterized, due to the lack of selective drugs. However, a role for P2X7R in regulating 5-HT release has been confirmed in more recent studies with genetic and pharmacological approaches, where it was reported that median raphe nuclei stimulation decreased the 5-HT release in the hippocampus of genetically deficient in P2X7R mice, and after perfusion with selective antagonists (JNJ-47965567 or AZ-10606120) [19]. In another study, however, P2X7R KO mice presents with increased hippocampal 5-HT levels, increased 5-HT transporter binding sites and 5-HT uptake, along with behavioral adaptation to stress [20].…”
Section: Mechanisms Regulated By P2x7 Receptor Signaling With Relementioning
confidence: 99%
See 1 more Smart Citation
“…However, the specific purinergic receptor subtype involved in this effect was not characterized, due to the lack of selective drugs. However, a role for P2X7R in regulating 5-HT release has been confirmed in more recent studies with genetic and pharmacological approaches, where it was reported that median raphe nuclei stimulation decreased the 5-HT release in the hippocampus of genetically deficient in P2X7R mice, and after perfusion with selective antagonists (JNJ-47965567 or AZ-10606120) [19]. In another study, however, P2X7R KO mice presents with increased hippocampal 5-HT levels, increased 5-HT transporter binding sites and 5-HT uptake, along with behavioral adaptation to stress [20].…”
Section: Mechanisms Regulated By P2x7 Receptor Signaling With Relementioning
confidence: 99%
“…The P2X7 receptor (P2X7R) is an ion channel activated by high concentrations of ATP, which for example can be observed following stress exposure [18]. The P2X7R has been involved in several process observed in MDD, such as impaired monoaminergic neurotransmission [19,20,21], increased glutamatergic neurotransmission [22], stimulation of a neuroinflammatory response [23] as well as reduced neuroplasticity [20,24]. In this scenario, the P2X7R becomes an interesting target for the understanding of depression neurobiology and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The DR, the developing Cb and the Ecu stand out for their known relationship with P2X7R activity. P2X7R has been shown to mediate the release of serotonin in the Hi through their activity in the raphe nucleus (Goloncser et al 2017 ). Regarding the Cb, we observed a strong P2rx7 -EGFP signal located in the EGL, known to produce granule neurons destined to reside in the internal granular layer (Alvarez Otero et al 1993 ; Hallonet et al 1990 ).…”
Section: Discussionmentioning
confidence: 99%
“…After 2 h equilibration period we collected 9 samples, one in every 30 min. Perfusion rate was 2 μl/min ( Figure 5 ) ( Goloncser et al, 2017 ). The first three samples served as baseline.…”
Section: Methodsmentioning
confidence: 99%
“…Method ( Goloncser et al, 2017 ). The extraction solution (PCA) was 0.1 M perchloric acid that contained theophylline (as an internal standard) at 10 mM concentration.…”
Section: Methodsmentioning
confidence: 99%